Pengaruh Pendidikan, PDRB, Angkatan Kerja dan Kemiskinan di Jawa Timur Tahun 2017 - Hindun Aisyah (Trunojoyo University of Madura, 2019)
The existence of the Suramadu Bridge can improve the economy in East Java, but the operation of the Suramadu Bridge has not been effective in reducing poverty in East Java. This can be seen from the poverty level of East Java of 11,49% higher than the average poverty Indonesia of 11,13%. The purpose of this study is to find out whether there is an effect of education, GRDP, and labor force on poverty and the factors that influence poverty in East Java in 2017. The method used is multiple linear regression analysis of cross section data. The analysis results indicate that education and labor force had a negative and significant effect on poverty while GRDP did not affect poverty in East Java.